Efektivitas Kebijakan Pemerintah Pembangunan Sejuta Rumah (Analisis Pembangunan Hunian Layak Di Kabupaten Bantul Tahun 2019) - Sadam, Muhammad; Angela, Deni; Asaduddin, Muhammad Salman; Rasya, Radhita; Salsabilla, Rita; Setiawanti, Shafira (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
The government's policy of building one million houses has been a major focus of Indonesia's efforts to improve access to decent housing for its citizens. Community access to the need for decent housing is a problem that must be immediately found a solution. For this reason, the government launched a one million house program in order to ensure the availability of decent houses for underprivileged residents. The purpose of this study is to evaluate as well as analyze the effectiveness of government policies to build one million houses, focusing on the analysis of rational housing development in Bantul province in 2019. The research method applied is qualitative research through a case study framework by collecting data from various sources relevant to the focus of the study.The results of the analysis show that the government's policy of building one million houses in Bantul Province has brought many positive results. Construction of decent housing has increased, increasing the number of houses built and increasing the availability of housing for low-income communities. However, there are also some hurdles that must be overcome, such as budget constraints and coordination between central and local governments. This study provides insight into the effectiveness of decent housing development policies in Bantul District. More research is needed to better understand the long-term impact of these policies and possible efforts to improve their efficiency and effectiveness.